High Frequency Modeling and Impedance Matching of Power Transformers for PLC Applications - Spahiu, Michael; Partal, Hakan P. (IEEE, 2014)
Over recent years Smart Grid communication applications in different frequency bands have been developed and used in the power utility industry. These applications consist of relay protection communication for high voltage equipment and distribution automation systems. Some research thus far has been focused on the modeling of power distribution lines in the medium to low voltage range. This paper will analyze the transmission of high frequency signals at MHz level thru a transformer and offer modeling techniques to better optimize the efficiency of the signals. This research contains a multidisciplinary approach to the power transformers for increased communication efficiency by designing matching networks in power lines. The objective of this paper is to help research in this particular topic and use this article as a starting point for future research in modeling of high frequency transformers for power line communication applications.
Keywords: Power Transformer; Smart Grid; Power Line Communications; Impedance Matching; RF Filtering; Computer Science